Aflatoxin B1 reported in herbal and traditional medicine and its risk assessment - Ab Dullah, Siti Soleha; Ahmad Sabri, Aida Nurul Ain; Mohd Pauzi, Nur Azra; Ab Hamid, Hasiah; Sabran, Mohd Redzwan; Abdullah, Rozaini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Aflatoxin B1 (AFB1) is a hepatotoxic and carcinogenic mycotoxin produced by Aspergillus species of fungi, mainly A. flavus and A. parasiticus. Ingestion of AFB1 is followed by gastrointestinal absorption and metabolism in the liver, leading to aflatoxicosis and progression of hepatocellular carcinoma (HCC). Objective: This study aims to perform the risk assessment of AFB1 contamination in herbal and traditional medicines using Margin of Exposure (MOE) approach. Methods: Secondary data were collected from animal toxicological data and AFB1 exposure from herbal and traditional medicine products worldwide. Animal dataset with dichotomous HCC endpoint was analysed using Benchmark Dose Software version 3.2 to derive the benchmark dose that gives 10% response (BMDL10 ). The estimated daily intake (EDI) was calculated based on daily assumption of 4.87 g AFB1 and 70 kg of body weight. Risk assessment was performed by calculating MOE with the ratio of BMDL10 and EDI for lifetime and 2 week exposure. Results: Of 244 samples of herbal and traditional medicine surveyed from the literature, 117 (48%) were contaminated with AFB1 above EU regulatory limit (>5 µg/kg). From this data, 226 of 244 (92%) samples had MOE values below 10,000 for lifetime exposure and the risk was 1950-fold lower for 2 week exposure following the Haber’s rule. Conclusion: : Majority of the herbal and traditional medicines contaminated with AFB1 had MOE lower than 10,000 indicating an urgency for risk management action. The production of herbal and traditional medicine should be monitored regularly to reduce the risk associated with AFB1.